Does laparoscopy have a limited role in diagnosis of fibroadhesive tuberculous peritonitis? - P. Wilairatana (2018)
The information on the limitations of laparoscopy (LP), particularly in the diagnosis of fibroadhesive form of tuberculous peritonitis (TP) is insufficient. Some reports suggested the risk and insufficient information obtained from LP in the diagnosis of fibroadhesive tuberculous peritonitis (FTP). The objectives of this study were to determine the usefulness and limitations of LP in the diagnosis of FTP and ascitic TP. The clinical and laparoscopic features of 64 patients with TP were analyzed. FTP was observed in 44 patients (68.8%) comprising 14 cases with small tubercles with thin fibrous adhesions in the peritoneum, 28 cases with large tubercles or confluent nodules with severe adhesions of intestinal loops omentum, and abdominal walls, and 2 cases with caseous material in the abdominal cavity with multiple peritoneal adhesions. Ascitic TP with multiple white nodules were found in 20 patients (31.2%). Laparoscopic diagnosis was confirmed by intralaparoscopic biopsies in all patients. No complications or limitations were found. Our study revealed that laparoscopy was a safe, accurate, and uncomplicated method for diagnosis of FTP and ascitic TP. It gave sufficient information, so diagnostic laparotomy was unnecessary.